Vehicle paint traceless repairing method

By using epoxy acrylate, guanosine triphosphate and linoleic acid modified painter repair paste, the problem of prone to cracking or peeling of traditional putty is solved, and better adhesion, durability and mechanical properties are achieved, and the service life of the repair paste is extended.

CN119909912APending Publication Date: 2025-05-02PAINTER (HENAN) COMMERCIAL OPERATION MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510172189.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The putty used in traditional car repair methods is prone to cracking or peeling over time, and cannot maintain the perfect state of the car paint for a long time.

Method used

The painter repair paste with epoxy acrylate, guanosine triphosphate and linoleic acid as the main body forms stable chemical bonds through the reaction of phosphate groups and the metal surface, improves adhesion, and improves thixotropy through the intermolecular action of long-chain fatty acids.

Benefits of technology

It significantly improves the adhesion, durability and mechanical properties of the painter repair paste, extends the durability of the repair paste, and optimizes the fluidity during construction and shape retention after curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of automobile coating, in particular to an automobile paint traceless repairing method which comprises the steps that S1.1, a scratch area is cleaned and polished; s1.2, painting design repairing paste is smeared on the scratches and cured; and S1.3, in combination with a flash drying technology, uniformly spraying transparent intermediate coat, finished paint and painter repair liquid in the repair area, using polishing wax to cooperate with a polishing machine for fine polishing, using a professional painter technique for manual finishing, and finally verifying through a paint film measuring instrument to complete traceless repair. By adopting the painter repairing paste, the adhesive force and the mechanical property of the repairing paste on the metal surface are improved, so that the durability of the painter repairing paste is prolonged, meanwhile, the thixotropy of the painter repairing paste is improved, and the surface repairing effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile painting, in particular to a method for seamlessly repairing automobile paint. Background Art

[0002] Seamless paint repair is an advanced automotive beauty technology that aims to restore the original gloss and flawless appearance of the vehicle's paint through a series of delicate and non-destructive operations. The core of this repair method is to accurately and meticulously treat minor damage to the paint surface (such as scratches, stains, oxide layers, etc.) without large-scale repainting or polishing, thereby avoiding possible problems such as reduced paint thickness, color changes or accelerated paint aging; however, the putty used in traditional car repair is prone to cracking or peeling over time. In view of this, we propose a seamless paint repair method. Summary of the invention

[0003] The purpose of the present invention is to provide a method for seamlessly repairing vehicle paint to solve the problems raised in the above-mentioned background technology.

[0004] To achieve the above object, the present invention provides a method for seamlessly repairing vehicle paint, comprising the following steps: S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 2000-3000 grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm-405nm and a light intensity of 1000-2000mW / cm² to irradiate the paint repair paste for 10-60s. After curing, use fine sandpaper for wet grinding, then rinse with water and wipe dry; the mass percentages of the paint repair paste components are: 30-40 parts by weight of adhesive matrix, 15-23 parts by weight of ethoxylated trimethylolpropane triacrylate, 1-5 parts by weight of xylene, 12-15 parts by weight of benzoin methyl ether, 5-7 parts by weight of isophorone diamine, 8-16 parts by weight of calcium carbonate, 15-25 parts by weight of talc, 12-23 parts by weight of diatomaceous earth and 1-8 parts by weight of titanium dioxide; S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 5-10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 10-15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 3-5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0005] Preferably, in S1.3, the mass percentages of the transparent mid-coat coating components are 30-35% acrylic copolymer, 16-20% polyurethane prepolymer, 5-7% xylene, 8-10% n-butanol, 8-12% ethyl acetate, 2-5% organosiloxane, 0.5-1.5% polyether modified silicone oil, 0.8-1.2% fumed silica, 8-10% heavy calcium carbonate and 10-12% talc.

[0006] Preferably, in S1.3, the mass percentages of the finished paint components are 18-24% of thermoplastic acrylic resin, 20-35% of two-component polyurethane resin, 18-30% of titanium dioxide, 10-15% of xylene, 8-12% of butyl acetate, 2-5% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.5-0.8% of perfluoropolyether, and 0.2-0.5% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate.

[0007] Preferably, in S1.3, the mass percentages of the components of the painter's repair liquid are 26-30% isophorone, 20-34% n-butyl acetate, 20-30% hexamethylene diisocyanate trimer, 3-8% nonylphenol polyoxyethylene ether, 2-5% triphenyl phosphate, 3-5% hydroxyethyl cellulose and 3-6% sodium benzoate.

[0008] Preferably, the steps for preparing the adhesive matrix are as follows: Under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution, which is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions. The mixture is stirred at room temperature for 20-30 minutes, and then the temperature is raised to 40-60°C and the reaction is continued for 4-6 hours. After the reaction is completed, the insoluble matter is filtered out to obtain a preliminary product, the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve it to form a mixed solution, and the reaction is stirred at room temperature for 8-12 hours. After the reaction is completed, an adhesive matrix is ​​obtained.

[0009] The epoxy group on epoxy acrylate can react with the amino group on guanosine triphosphate and then connect to epoxy acrylate. Guanosine triphosphate contains a phosphate group. Since the phosphate group has good metal surface affinity, it can form a stable complex with the metal surface and react with the hydroxyl group on the metal surface to form a chemical bond. Therefore, it can effectively improve the adhesion of epoxy acrylate to the metal substrate and form a phosphating film on the metal surface to provide an additional protective layer. Since the painter's repair paste contains amine curing agents, the phosphate group can cross-link with the amino group to form a more complex network structure, thereby enhancing the internal strength of the repair paste and improving its adhesion to other components. However, guanosine triphosphate is water-soluble, while epoxy acrylate is oil-soluble. There are compatibility issues between them, so linoleic acid is introduced.

[0010] Linoleic acid is an unsaturated long-chain fatty acid with antioxidant capacity, thus delaying the aging process of the repair cream. In addition, the hydrophobic long chain can improve the compatibility of guanosine triphosphate and epoxy acrylate, and can also give the repair cream better thixotropy, that is, the viscosity decreases under shear force, and the viscosity recovers under static state. Specifically, there are a variety of intermolecular forces between long-chain fatty acid molecules and between them and other ingredients in the repair cream, including van der Waals forces, hydrogen bonds and hydrophobic interactions. These weak interactions can make fatty acid molecules form a loose but ordered network structure in the absence of external forces, and the carbon chain part of the long-chain fatty acid The particles have a large spatial volume and can play a role similar to a "scaffold" in the material, hindering the free movement of molecules, thereby increasing the viscosity in a static state. When shear force is applied, by brushing or scraping, these external forces are sufficient to overcome the weak interactions between molecules, causing the network structure formed above to temporarily disintegrate. With the destruction of the network structure, the relative movement between molecules becomes easier, so the material exhibits a lower viscosity and is easy to flow and spread. Once the shear force is removed, the weak interactions between molecules are quickly re-established, restoring the material to its original high viscosity state, thus helping the fluidity during construction and maintaining the shape after final curing.

[0011] Preferably, the molar concentration of the guanosine triphosphate solution is 15-20 mM.

[0012] Preferably, the mass ratio of the N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:4-6, and the mass ratio of the 4-dimethylaminopyridine to guanosine triphosphate is 1.6-1.8%.

[0013] Preferably, the adhesive matrix is ​​prepared by mixing epoxy acrylate, guanosine triphosphate and linoleic acid in a mass ratio of 1.5:2.1-3.7:0.8-1.2.

[0014] Preferably, the mass fraction of the mixed solution is 12-20%.

[0015] Preferably, in said S1.2, the mass percentage of the components in the preparation steps of the paint repair paste are specifically: Pour the adhesive base, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talc, diatomaceous earth and titanium dioxide in sequence at a speed of 300-600rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, and continue stirring for 10-15 minutes to evenly mix all the ingredients. Finally, put the mixture into a vacuum degassing machine to remove bubbles for 10-20 minutes to obtain the paint repair paste.

[0016] Compared with the prior art, the present invention has the following beneficial effects: In the method for seamless repair of vehicle paint, a paint repair paste composed mainly of epoxy acrylate, guanosine triphosphate and linoleic acid is used. The complexing ability of the phosphate group with the metal and the active reaction ability of the hydroxyl group on the metal surface are utilized to form a stable chemical bond, thereby improving the adhesion of the repair paste on the metal surface, thereby extending the durability of the paint repair paste. The cross-linking reaction of the phosphate group and the amino group is utilized to promote the formation of a more complex network structure, thereby enhancing the internal strength of the repair paste. The hydrophobicity of the long-chain fatty group is utilized to improve the compatibility of guanosine triphosphate with epoxy acrylate, and the thixotropy of the paint repair paste is improved through the intermolecular force of the long-chain fatty acid. The paint repair paste has good mechanical properties and metal adhesion, is easy to construct, reduces sagging and dripping, and thus improves the surface repair effect. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] A method for seamlessly repairing vehicle paint of the present invention comprises the following steps: S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 2000-3000 grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm-405nm and a light intensity of 1000-2000mW / cm² to irradiate the paint repair paste for 10-60s. After curing, use fine sandpaper for wet sanding, then rinse with water and wipe dry; S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 5-10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 10-15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 3-5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0019] The polishing wax used in the following embodiments is CHARO GARCIA water-based polishing wax.

[0020] Embodiment 1: A method for seamlessly repairing vehicle paint, wherein: The weight percentages of the components of the paint repair paste are: 40 parts by weight of adhesive base, 23 parts by weight of ethoxylated trimethylolpropane triacrylate, 5 parts by weight of xylene, 15 parts by weight of benzoin methyl ether, 7 parts by weight of isophorone diamine, 16 parts by weight of calcium carbonate, 25 parts by weight of talc, 23 parts by weight of diatomaceous earth and 8 parts by weight of titanium dioxide; The adhesive matrix is ​​prepared by mixing epoxy acrylate, guanosine triphosphate and linoleic acid in a mass ratio of 1.5:2.1:0.8; the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:6; the mass ratio of 4-dimethylaminopyridine to guanosine triphosphate is 1.8%; Among them, the mass percentage of the transparent mid-coat component is 32% of acrylic copolymer, 18% of polyurethane prepolymer, 6% of xylene, 9% of n-butanol, 10% of ethyl acetate, 3% of organosiloxane, 1% of polyether modified silicone oil, 1% of fumed silica, 9% of heavy calcium carbonate, and 11% of talc; the mass percentage of the finished paint component is 22% of thermoplastic acrylic resin, 28% of two-component polyurethane resin, 26% of titanium dioxide, 11% of xylene, 8-12% of butyl acetate, 3% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.6% of perfluoropolyether, and 0.4% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate; the mass percentage of the paint repair liquid component is 28% of isophorone, 29% of n-butyl acetate, 26% of hexamethylene diisocyanate trimer, 5% of nonylphenol polyoxyethylene ether, 3% of triphenyl phosphate, 4% of hydroxyethyl cellulose, and 5% of sodium benzoate; The specific steps are as follows: under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution with a molar concentration of 15mM, and the solution is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions, and the solution is stirred at room temperature for 30 minutes, and then the temperature is raised to 60°C and the reaction is continued for 6 hours. After the reaction is completed, the insoluble matter is filtered to remove the preliminary product, and the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve the mixed solution to form a mixed solution with a mass fraction of 12%, and the reaction is stirred at room temperature for 12 hours. After the reaction is completed, an adhesive matrix is ​​obtained; Pour the adhesive matrix, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talcum powder, diatomaceous earth and titanium dioxide in sequence at a speed of 500 rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, continue stirring for 15 minutes to evenly mix all the ingredients, and finally put the mixture into a vacuum degassing machine to remove bubbles for 10 minutes to obtain a paint repair paste; S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 3000-grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm and a light intensity of 2000mW / cm² to irradiate the paint repair paste for 30s. After curing, use fine sandpaper for wet sanding, then rinse with water and wipe dry. S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0021] Embodiment 2: A method for seamlessly repairing vehicle paint, wherein: The weight percentages of the components of the paint repair paste are: 40 parts by weight of adhesive base, 23 parts by weight of ethoxylated trimethylolpropane triacrylate, 5 parts by weight of xylene, 15 parts by weight of benzoin methyl ether, 7 parts by weight of isophorone diamine, 16 parts by weight of calcium carbonate, 25 parts by weight of talc, 23 parts by weight of diatomaceous earth and 8 parts by weight of titanium dioxide; The adhesive matrix is ​​prepared by mixing epoxy acrylate with guanosine triphosphate and linoleic acid in a mass ratio of 1.5:2.9:1; the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:6; the mass ratio of 4-dimethylaminopyridine to guanosine triphosphate is 1.8%; Among them, the mass percentage of the transparent mid-coat component is 32% of acrylic copolymer, 18% of polyurethane prepolymer, 6% of xylene, 9% of n-butanol, 10% of ethyl acetate, 3% of organosiloxane, 1% of polyether modified silicone oil, 1% of fumed silica, 9% of heavy calcium carbonate, and 11% of talc; the mass percentage of the finished paint component is 22% of thermoplastic acrylic resin, 28% of two-component polyurethane resin, 26% of titanium dioxide, 11% of xylene, 8-12% of butyl acetate, 3% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.6% of perfluoropolyether, and 0.4% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate; the mass percentage of the paint repair liquid component is 28% of isophorone, 29% of n-butyl acetate, 26% of hexamethylene diisocyanate trimer, 5% of nonylphenol polyoxyethylene ether, 3% of triphenyl phosphate, 4% of hydroxyethyl cellulose, and 5% of sodium benzoate; The specific steps are as follows: under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution with a molar concentration of 15mM, and the solution is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions, and the solution is stirred at room temperature for 30 minutes, and then the temperature is raised to 60°C and the reaction is continued for 6 hours. After the reaction is completed, the insoluble matter is filtered to remove the preliminary product, and the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve the mixed solution to form a mixed solution with a mass fraction of 12%, and the reaction is stirred at room temperature for 12 hours. After the reaction is completed, an adhesive matrix is ​​obtained; Pour the adhesive matrix, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talcum powder, diatomaceous earth and titanium dioxide in sequence at a speed of 500 rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, continue stirring for 15 minutes to evenly mix all the ingredients, and finally put the mixture into a vacuum degassing machine to remove bubbles for 10 minutes to obtain a paint repair paste; S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 3000-grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm and a light intensity of 2000mW / cm² to irradiate the paint repair paste for 30s. After curing, use fine sandpaper for wet sanding, then rinse with water and wipe dry. S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0022] Embodiment 3: A method for seamlessly repairing vehicle paint, wherein: The weight percentages of the components of the paint repair paste are: 40 parts by weight of adhesive base, 23 parts by weight of ethoxylated trimethylolpropane triacrylate, 5 parts by weight of xylene, 15 parts by weight of benzoin methyl ether, 7 parts by weight of isophorone diamine, 16 parts by weight of calcium carbonate, 25 parts by weight of talc, 23 parts by weight of diatomaceous earth, 5 parts by weight of xylene and 8 parts by weight of titanium dioxide; The adhesive matrix is ​​prepared by mixing epoxy acrylate, guanosine triphosphate and linoleic acid in a mass ratio of 1.5:3.7:1.2; the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:6; the mass ratio of 4-dimethylaminopyridine to guanosine triphosphate is 1.8%; Among them, the mass percentage of the transparent mid-coat component is 32% of acrylic copolymer, 18% of polyurethane prepolymer, 6% of xylene, 9% of n-butanol, 10% of ethyl acetate, 3% of organosiloxane, 1% of polyether modified silicone oil, 1% of fumed silica, 9% of heavy calcium carbonate, and 11% of talc; the mass percentage of the finished paint component is 22% of thermoplastic acrylic resin, 28% of two-component polyurethane resin, 26% of titanium dioxide, 11% of xylene, 8-12% of butyl acetate, 3% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.6% of perfluoropolyether, and 0.4% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate; the mass percentage of the paint repair liquid component is 28% of isophorone, 29% of n-butyl acetate, 26% of hexamethylene diisocyanate trimer, 5% of nonylphenol polyoxyethylene ether, 3% of triphenyl phosphate, 4% of hydroxyethyl cellulose, and 5% of sodium benzoate; The specific steps are as follows: under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution with a molar concentration of 15mM, and the solution is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions, and the solution is stirred at room temperature for 30 minutes, and then the temperature is raised to 60°C and the reaction is continued for 6 hours. After the reaction is completed, the insoluble matter is filtered to remove the preliminary product, and the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve the mixed solution to form a mixed solution with a mass fraction of 12%, and the reaction is stirred at room temperature for 12 hours. After the reaction is completed, an adhesive matrix is ​​obtained; Pour the adhesive matrix, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talcum powder, diatomaceous earth and titanium dioxide in sequence at a speed of 500 rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, continue stirring for 15 minutes to evenly mix all the ingredients, and finally put the mixture into a vacuum degassing machine to remove bubbles for 10 minutes to obtain a paint repair paste; S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 3000-grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm and a light intensity of 2000mW / cm² to irradiate the paint repair paste for 30s. After curing, use fine sandpaper for wet sanding, then rinse with water and wipe dry. S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0023] Embodiment 4: A method for seamlessly repairing vehicle paint, wherein: The weight percentages of the components of the paint repair paste are: 40 parts by weight of adhesive base, 15 parts by weight of ethoxylated trimethylolpropane triacrylate, 1 part by weight of xylene, 12 parts by weight of benzoin methyl ether, 5 parts by weight of isophorone diamine, 8 parts by weight of calcium carbonate, 15 parts by weight of talc, 12 parts by weight of diatomaceous earth and 1 part by weight of titanium dioxide; The adhesive matrix is ​​prepared by mixing epoxy acrylate, guanosine triphosphate and linoleic acid in a mass ratio of 1.5:3.7:1.2; the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:6; the mass ratio of 4-dimethylaminopyridine to guanosine triphosphate is 1.8%; Among them, the mass percentage of the transparent mid-coat component is 32% of acrylic copolymer, 18% of polyurethane prepolymer, 6% of xylene, 9% of n-butanol, 10% of ethyl acetate, 3% of organosiloxane, 1% of polyether modified silicone oil, 1% of fumed silica, 9% of heavy calcium carbonate, and 11% of talc; the mass percentage of the finished paint component is 22% of thermoplastic acrylic resin, 28% of two-component polyurethane resin, 26% of titanium dioxide, 11% of xylene, 8-12% of butyl acetate, 3% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.6% of perfluoropolyether, and 0.4% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate; the mass percentage of the paint repair liquid component is 28% of isophorone, 29% of n-butyl acetate, 26% of hexamethylene diisocyanate trimer, 5% of nonylphenol polyoxyethylene ether, 3% of triphenyl phosphate, 4% of hydroxyethyl cellulose, and 5% of sodium benzoate; The specific steps are as follows: under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution with a molar concentration of 15mM, and the solution is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions, and the solution is stirred at room temperature for 30 minutes, and then the temperature is raised to 60°C and the reaction is continued for 6 hours. After the reaction is completed, the insoluble matter is filtered to remove the preliminary product, and the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve the mixed solution to form a mixed solution with a mass fraction of 12%, and the reaction is stirred at room temperature for 12 hours. After the reaction is completed, an adhesive matrix is ​​obtained; Pour the adhesive matrix, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talcum powder, diatomaceous earth and titanium dioxide in sequence at a speed of 500 rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, continue stirring for 15 minutes to evenly mix all the ingredients, and finally put the mixture into a vacuum degassing machine to remove bubbles for 10 minutes to obtain a paint repair paste; S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 3000-grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm and a light intensity of 2000mW / cm² to irradiate the paint repair paste for 30s. After curing, use fine sandpaper for wet sanding, then rinse with water and wipe dry. S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0024] Embodiment 5: A method for seamlessly repairing vehicle paint, wherein: The weight percentages of the components of the paint repair paste are: 30 parts by weight of adhesive base, 23 parts by weight of ethoxylated trimethylolpropane triacrylate, 5 parts by weight of xylene, 15 parts by weight of benzoin methyl ether, 7 parts by weight of isophorone diamine, 16 parts by weight of calcium carbonate, 25 parts by weight of talc, 23 parts by weight of diatomaceous earth and 8 parts by weight of titanium dioxide; The adhesive matrix is ​​prepared by mixing epoxy acrylate, guanosine triphosphate and linoleic acid in a mass ratio of 1.5: 3.7: 1.2; the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:6; the mass ratio of 4-dimethylaminopyridine to guanosine triphosphate is 1.8%; Among them, the mass percentage of the transparent mid-coat component is 32% of acrylic copolymer, 18% of polyurethane prepolymer, 6% of xylene, 9% of n-butanol, 10% of ethyl acetate, 3% of organosiloxane, 1% of polyether modified silicone oil, 1% of fumed silica, 9% of heavy calcium carbonate, and 11% of talc; the mass percentage of the finished paint component is 22% of thermoplastic acrylic resin, 28% of two-component polyurethane resin, 26% of titanium dioxide, 11% of xylene, 8-12% of butyl acetate, 3% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.6% of perfluoropolyether, and 0.4% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate; the mass percentage of the paint repair liquid component is 28% of isophorone, 29% of n-butyl acetate, 26% of hexamethylene diisocyanate trimer, 5% of nonylphenol polyoxyethylene ether, 3% of triphenyl phosphate, 4% of hydroxyethyl cellulose, and 5% of sodium benzoate; The specific steps are as follows: under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution with a molar concentration of 15mM, and the solution is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions, and the solution is stirred at room temperature for 30 minutes, and then the temperature is raised to 60°C and the reaction is continued for 6 hours. After the reaction is completed, the insoluble matter is filtered to remove the preliminary product, and the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve the mixed solution to form a mixed solution with a mass fraction of 12%, and the reaction is stirred at room temperature for 12 hours. After the reaction is completed, an adhesive matrix is ​​obtained; Pour the adhesive matrix, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talcum powder, diatomaceous earth and titanium dioxide in sequence at a speed of 500 rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, continue stirring for 15 minutes to evenly mix all the ingredients, and finally put the mixture into a vacuum degassing machine to remove bubbles for 10 minutes to obtain a paint repair paste; S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 3000-grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm and a light intensity of 2000mW / cm² to irradiate the paint repair paste for 30s. After curing, use fine sandpaper for wet sanding, then rinse with water and wipe dry. S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0025] Embodiment 6: A method for seamlessly repairing vehicle paint, wherein: The weight percentages of the components of the paint repair paste are: 35 parts by weight of adhesive base, 23 parts by weight of ethoxylated trimethylolpropane triacrylate, 5 parts by weight of xylene, 15 parts by weight of benzoin methyl ether, 7 parts by weight of isophorone diamine, 16 parts by weight of calcium carbonate, 25 parts by weight of talc, 23 parts by weight of diatomaceous earth and 8 parts by weight of titanium dioxide; The adhesive matrix is ​​prepared by mixing epoxy acrylate, guanosine triphosphate and linoleic acid in a mass ratio of 1.5: 3.7: 1.2; the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:6; the mass ratio of 4-dimethylaminopyridine to guanosine triphosphate is 1.8%; Among them, the mass percentage of the transparent mid-coat component is 32% of acrylic copolymer, 18% of polyurethane prepolymer, 6% of xylene, 9% of n-butanol, 10% of ethyl acetate, 3% of organosiloxane, 1% of polyether modified silicone oil, 1% of fumed silica, 9% of heavy calcium carbonate, and 11% of talc; the mass percentage of the finished paint component is 22% of thermoplastic acrylic resin, 28% of two-component polyurethane resin, 26% of titanium dioxide, 11% of xylene, 8-12% of butyl acetate, 3% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.6% of perfluoropolyether, and 0.4% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate; the mass percentage of the paint repair liquid component is 28% of isophorone, 29% of n-butyl acetate, 26% of hexamethylene diisocyanate trimer, 5% of nonylphenol polyoxyethylene ether, 3% of triphenyl phosphate, 4% of hydroxyethyl cellulose, and 5% of sodium benzoate; The specific steps are as follows: under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution with a molar concentration of 15mM, and the solution is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions, and the solution is stirred at room temperature for 30 minutes, and then the temperature is raised to 60°C and the reaction is continued for 6 hours. After the reaction is completed, the insoluble matter is filtered to remove the preliminary product, and the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve the mixed solution to form a mixed solution with a mass fraction of 12%, and the reaction is stirred at room temperature for 12 hours. After the reaction is completed, an adhesive matrix is ​​obtained; Pour the adhesive matrix, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talcum powder, diatomaceous earth and titanium dioxide in sequence at a speed of 500 rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, continue stirring for 15 minutes to evenly mix all the ingredients, and finally put the mixture into a vacuum degassing machine to remove bubbles for 10 minutes to obtain a paint repair paste; S1.1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 3000-grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm and a light intensity of 2000mW / cm² to irradiate the paint repair paste for 30s. After curing, use fine sandpaper for wet sanding, then rinse with water and wipe dry. S1.3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

[0026] Comparative Example 1: The method of Example 3 was adopted, and the painter's repair paste was replaced by ordinary putty.

[0027] Comparative Example 2: The method of Example 3 was adopted to directly use epoxy acrylate without modifying the epoxy acrylate by guanosine triphosphate and linoleic acid.

[0028] Comparative Example 3: The method of Example 3 was adopted, epoxy acrylate and guanosine triphosphate were used directly, and epoxy acrylate and guanosine triphosphate were not modified by linoleic acid.

[0029] The present invention adopts a paint repair paste in the method for seamlessly repairing vehicle paint prepared by using an adhesive matrix, wherein the performance index inspection items and inspection standards of the paint repair paste are as follows: According to GB / T 2792-2014 "Test method for peel strength of adhesive tape", the paint repair paste is evenly coated on the surface of the metal plate and cured. The metal plate is fixed in a fixture of the tensile testing machine. The other fixture of the testing machine clamps the free end of the adhesive tape, which is 180° to the stainless steel plate. The adhesive tape is pulled apart at a rate of 100 mm / min. The peeling force is measured by the force required to continuously peel the adhesive tape from the stainless steel plate and converted into adhesion to characterize the affinity of the paint repair paste to the metal. The sample is placed in a 60°C and -20°C climate aging test chamber to complete a complete high and low temperature cycle every 24 hours. After 5 cycles, the adhesion is tested again to observe its changes and characterize its durability. Prepare a specimen with a width of 10 mm, a length of 150 mm and a thickness of 2 mm, fix the specimen between the upper and lower fixtures of the universal material testing machine, start the testing machine, and stretch the specimen at a speed of 5 mm / min until it breaks, and record the tensile strength.

[0030] According to the above standards, the paint repair paste in the method for seamless repair of vehicle paint prepared in the above Examples 1-6 and Comparative Examples 1-3 was tested, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3 The above data fully demonstrate that compared with Comparative Examples 1-3, Examples 1-6 can fully show the effect of the adhesive matrix on the adhesion, durability and mechanical properties of the painter's repair paste in the vehicle paint seamless repair method.

[0031] Since the paint repair paste prepared by the present invention adopts the adhesive matrix, the adhesion, durability and mechanical properties of the paint repair paste are effectively improved by the adhesive matrix, as follows: It can be seen from Examples 1-3 that with the continuous increase in the proportion of the adhesive matrix component, the adhesion, durability and mechanical properties of the painter's repair paste gradually increase. Since the amino group on guanosine triphosphate can react with the epoxy group on epoxy acrylate, the more guanosine triphosphate content there is, the stronger its chemical bonding is, and the more phosphate groups there are, the better the reaction activity with the hydroxyl or other functional groups on the metal surface, the higher the affinity for the metal surface, and the stability of the overall structure is also improved. The presence of linoleic acid not only improves the compatibility between water-soluble components and oil-soluble components, but also its long-chain structure can construct an ordered intermolecular network inside the material, thereby optimizing the thixotropy of the painter's repair paste and giving the material better flexibility and impact resistance.

[0032] It can be seen from Examples 3 and 4 that with the continuous increase in the content of other components, the adhesion, durability and mechanical properties of the painter's repair paste do not change significantly, which shows that small changes in other components within a certain range are not enough to cause significant changes in the adhesion, durability and mechanical properties of the painter's repair paste. Therefore, the key factor that determines the adhesion, durability and mechanical properties of the painter's repair paste is the adhesive matrix.

[0033] It can be seen from Examples 3, 5 and 6 that as the content of the adhesive matrix continues to change, the adhesion, durability and mechanical properties of the paint repair paste continue to change. The adhesive matrix is ​​the basic skeleton provider of the paint repair paste, providing basic mechanical strength and support structure for the entire system, and covalently bonding with other functional molecules guanosine triphosphate and linoleic acid to form a more stable composite material. The special interaction between the phosphate group and the metal surface greatly improves the adhesion of the repair paste to the metal substrate. Linoleic acid acts as a bridge, allowing compounds of different polarities to coexist and be evenly distributed in the same system, and the long-chain structure gives the repair paste good thixotropy. Therefore, the increase in the main content of the adhesive matrix, the better the adhesion, durability and mechanical properties of the paint repair paste.

[0034] According to the above test experiments, the paint repair paste in the method for seamless repair of car paint prepared according to Example 3 has the best performance, so Example 3 is taken as the best example; By comparing Example 3 with Comparative Examples 1-3, it can be seen that: In Comparative Example 1, the paint repair paste is replaced with ordinary putty. The adhesion, durability and mechanical properties of the paint repair paste are poor. Although ordinary putty has certain adhesion, it lacks the special modified components of the adhesive matrix, namely the phosphate group and the long-chain structure, and cannot provide the same adhesion, thixotropy and mechanical properties. Therefore, the adhesion, durability and mechanical properties of the paint repair paste are poor.

[0035] Comparative Example 2 directly uses epoxy acrylate without modifying the epoxy acrylate through guanosine triphosphate and linoleic acid. The adhesion, durability and mechanical properties of the paint repair paste are poor. The unmodified epoxy acrylate lacks additional active sites for reacting with the metal surface, and its chemical bonding strength is reduced, and its affinity with the metal is reduced, and thus its durability is also reduced. It also lacks the thixotropy provided by the long-chain structure. Therefore, the adhesion, durability and mechanical properties of the paint repair paste are poor.

[0036] Comparative Example 3 directly uses epoxy acrylate and guanosine triphosphate, and epoxy acrylate and guanosine triphosphate are not modified by linoleic acid. The adhesion, durability and mechanical properties of the painter's repair paste are poor. Therefore, although guanosine triphosphate can improve the adhesion of epoxy acrylate to the metal substrate, it is water-soluble and has compatibility issues with oil-soluble epoxy acrylate, resulting in poor mixing effect of the two, which in turn affects the overall performance. In addition, linoleic acid gives the repair paste better thixotropy, which can maintain a high viscosity in a static state and is easy to flow under shear force. Therefore, the adhesion, durability and mechanical properties of the painter's repair paste are poor.

[0037] In summary, the painter's repair paste prepared by the adhesive matrix has excellent adhesion, durability and mechanical properties. By introducing phosphate groups and long-chain structures into epoxy acrylate, the affinity with the metal surface can be improved, and the thixotropy of the painter's repair paste can be improved, which is beneficial to the bonding strength, durability and surface repair effect of the painter's repair paste on the metal surface.

[0038] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for seamless repair of vehicle paint, characterized in that: The steps include: S1.

1. Use car cleaning agent to thoroughly clean the scratched area and its surroundings to remove oil, dust and other impurities, wipe dry with a microfiber cloth, and then use 2000-3000 grit fine sandpaper to sand the paint surface around the scratch to make it smooth. After sanding, clean again and make sure the surface is dry, and then use masking tape to cover the area that does not need to be repaired; S1.

2. Use a scraping tool to apply the paint repair paste on the scratches and make it flush with the original car paint surface. Use a UV lamp with a wavelength of 365nm-405nm and a light intensity of 1000-2000mW / cm² to irradiate the paint repair paste for 10-60s. After curing, use fine sandpaper for wet grinding, then rinse with water and wipe dry; the mass percentages of the paint repair paste components are: 30-40 parts by weight of adhesive matrix, 15-23 parts by weight of ethoxylated trimethylolpropane triacrylate, 1-5 parts by weight of xylene, 12-15 parts by weight of benzoin methyl ether, 5-7 parts by weight of isophorone diamine, 8-16 parts by weight of calcium carbonate, 15-25 parts by weight of talc, 12-23 parts by weight of diatomaceous earth and 1-8 parts by weight of titanium dioxide; S1.

3. Use a spray gun to evenly spray a layer of transparent mid-coat on the cured repair area, and use the flash-drying technology of the painter's quick drying equipment to dry it for 5-10 minutes. Then spray the finished paint evenly on the transparent mid-coat, and continue to use the flash-drying technology to dry it for 10-15 minutes. After spraying the finished paint, apply a layer of painter's repair liquid on the edge of the repair area to reduce the interface mark, flash dry for 3-5 minutes, and then polish and clean with fine sandpaper. Use polishing wax and a polishing machine to finely polish the repair area. Finally, use professional painter techniques to perform manual finishing and verify with a paint film measuring instrument. The car paint has been repaired seamlessly.

2. A method for seamless repair of vehicle paint according to claim 1, characterized in that: In S1.3, the mass percentages of the transparent mid-coat coating components are 30-35% of acrylic copolymer, 16-20% of polyurethane prepolymer, 5-7% of xylene, 8-10% of n-butanol, 8-12% of ethyl acetate, 2-5% of organic siloxane, 0.5-1.5% of polyether modified silicone oil, 0.8-1.2% of fumed silica, 8-10% of heavy calcium carbonate and 10-12% of talc.

3. A method for seamlessly repairing vehicle paint according to claim 1, characterized in that: In S1.3, the mass percentages of the finished paint components are 18-24% of thermoplastic acrylic resin, 20-35% of two-component polyurethane resin, 18-30% of titanium dioxide, 10-15% of xylene, 8-12% of butyl acetate, 2-5% of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.5-0.8% of perfluoropolyether, and 0.2-0.5% of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate.

4. A method for seamlessly repairing vehicle paint according to claim 1, characterized in that: In S1.3, the mass percentages of the components of the painter's repair liquid are 26-30% of isophorone, 20-34% of n-butyl acetate, 20-30% of hexamethylene diisocyanate trimer, 3-8% of nonylphenol polyoxyethylene ether, 2-5% of triphenyl phosphate, 3-5% of hydroxyethyl cellulose and 3-6% of sodium benzoate.

5. A method for seamlessly repairing vehicle paint according to claim 1, characterized in that: The steps of preparing the adhesive matrix are specifically as follows: Under nitrogen protection, guanosine triphosphate is dissolved in dimethylformamide to form a guanosine triphosphate solution, which is continuously stirred with a stirrer, and then N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added, and linoleic acid is gradually added under stirring conditions. The mixture is stirred at room temperature for 20-30 minutes, and then the temperature is raised to 40-60°C and the reaction is continued for 4-6 hours. After the reaction is completed, the insoluble matter is filtered out to obtain a preliminary product, the preliminary product is mixed with epoxy acrylate, and dimethylformamide is added to dissolve it to form a mixed solution, and the reaction is stirred at room temperature for 8-12 hours. After the reaction is completed, an adhesive matrix is ​​obtained.

6. A method for seamlessly repairing vehicle paint according to claim 5, characterized in that: The molar concentration of the guanosine triphosphate solution is 15-20 mM.

7. A method for seamlessly repairing vehicle paint according to claim 5, characterized in that: The mass ratio of the added amount of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to guanosine triphosphate is 1:4-6, and the added amount of 4-dimethylaminopyridine is 1.6-1.8% of the mass of guanosine triphosphate.

8. A method for seamlessly repairing vehicle paint according to claim 5, characterized in that: The adhesive matrix is ​​prepared by mixing epoxy acrylate, guanosine triphosphate and linoleic acid in a mass ratio of 1.5:2.1-3.7:0.8-1.

2.

9. A method for seamlessly repairing vehicle paint according to claim 5, characterized in that: The mass fraction of the mixed solution is 12-20%.

10. A method for seamlessly repairing vehicle paint according to claim 1, characterized in that: The steps for preparing the paint repair paste by mass percentage of the components in S1.2 are as follows: Pour the adhesive base, ethoxylated trimethylolpropane triacrylate and xylene into a stirring container, start the stirrer, add calcium carbonate, talc, diatomaceous earth and titanium dioxide in sequence at a speed of 300-600rpm to ensure that they are completely dispersed, then add benzoin methyl ether and isophorone diamine, and continue stirring for 10-15 minutes to evenly mix all the ingredients. Finally, put the mixture into a vacuum degassing machine to remove bubbles for 10-20 minutes to obtain the paint repair paste.